Wage-productivity gap in OECD economies - Ceyhun Elgin; Tolga Umut Kuzubas (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The Walrasian theory of labor market equilibrium predicts that in the absence of any market frictions, workers earn a wage rate equal to their marginal productivity. In this paper, based on the neoclassical tradition, the authors define the ratio of the marginal product of labor to real wages as the Pigouvian exploitation rate and then construct a panel dataset of this specific wage-productivity gap for the manufacturing sector in OECD economies. Next, they investigate its relationship with the unemployment rate along with various other variables such as the government taxation, capital expansion, unionization, inflation. Their findings suggest that the wage-productivity gap gives a robust and significantly positive response to shocks to unemployment rate and a negative response to shocks to unionization.
Keywords: J24; J30; J64; 330; wages; marginal productivity of labor; panel-VAR; OECD economies; Lohnniveau; Arbeitsproduktivität; Marginalanalyse; Panel; VAR-Modell; OECD-Staaten